2007
DOI: 10.5551/jat.e498
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Term Exercise on Adiponectin and Adiponectin Receptor Levels in Rats

Abstract: Aim: Adiponectin reportedly reduces insulin resistance. Exercise has also been shown to lessen insulin resistance, although it is not well known whether exercise increases levels of adiponectin and/or its receptors nor whether it effects are dependent on exercise intensity and/or period. We previously reported that blood adiponectin levels increased by 150% in animals that exercised at a rate of 30 m/min for 60 minutes, 2 days per week, and adiponectin receptor 1 (AdipoR1) mRNA levels in muscle increased up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…There is interplay between the oxidation of lipids and carbohydrates during exercise, with lower intensities associated with a greater percentage of FFAs oxidation and higher intensities with greater carbohydrate utilization; exercise intensity also affects the reliance on the form (glycogen or glucose) of carbohydrate oxidized [51]. In studies using rodent, adiponectin has been shown to regulate plasma FFAs clearance by stimulating skeletal muscle FFA uptake [52] and/or oxidation [53]. Our results showed in the diabetic ZDF rats that underwent acute strenuous exercise an augment of adiponectin levels (+5.8%; P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…There is interplay between the oxidation of lipids and carbohydrates during exercise, with lower intensities associated with a greater percentage of FFAs oxidation and higher intensities with greater carbohydrate utilization; exercise intensity also affects the reliance on the form (glycogen or glucose) of carbohydrate oxidized [51]. In studies using rodent, adiponectin has been shown to regulate plasma FFAs clearance by stimulating skeletal muscle FFA uptake [52] and/or oxidation [53]. Our results showed in the diabetic ZDF rats that underwent acute strenuous exercise an augment of adiponectin levels (+5.8%; P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…A recent clinical interventional study demonstrated that the increase in adiponectin concentration in response to physical exercise was related to a reduction in fat mass and inflammatory factor levels 24) . Adiponectin mRNA levels in epididymal fat tissue increased in rats after treadmill exercise 25) . Furthermore, 3T3-L1 adipocytes treated with TNF-showed decreased adiponectin mRNA expression 26) , suggesting that TNF- Serum IL-6 and TNF-levels were measured using the Cytometric Bead Array Mouse Soluble Protein Master Buffer Kit in the STD (n 8), HFD (n 6), and HFD Ex (n 6) groups at 18 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased effects of adiponectin on glucose uptake coupled with the acceleration of fatty acid oxidation, observed in current study, suggest an increase in very low density lipoprotein receptor expression and/or a decrease in the AdipoR1/R2 ratio in patients with a high HMWadiponectin concentration. In addition, adiponectin receptor mRNA expression was reported to correlate with diet and exercise 39,40) . Differences in the expression of these receptors need to be studied to clarify the influences of HMW-adiponectin on insulin therapy in patients with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%